Hubungan gaya belajar visual, auditorialDan kinestetik dengan hasil belajar matematika(Studi Asosiatif pada Siswa Kelas XI Sekolah Menengah KejuruanNegeri 9 Surakarta Tahun Pelajaran 2015/2016) - Marfu'ah, Zuroh (2016)
The study aims at evaluating: an relation between learning styles with learning outcomes. Learning styles are visual, auditory and kinesthetic. This study is a quantitative research design associative research. The population of this study is 453 students of 11th grade of SMK N 9 Surakarta. Samples taken is 11th grade of Visual Communication Design as many as 29 students consisting of 15 male students and 14 female students. The sampling technique used purposive sampling technique. The data collection techniques used methods of questionnaires and documentation. Data analysis techniques used using contingency coefficient with a significance level of 5%. Based komputed the conclusion is no relation between learning styles on student's mathematics with learning outcomes.